A Cu based layered multifunctional material: (C8H12N)2CuCl4 Optical and electronic properties. (11th July 2018) - Kassou, Said; Belaaraj, Abdesselam
Abstract: Toward the processing of a multifunctional material, single crystals of PEA-CuCl4 [PEA = (C6 H5 -C2 H4 -NH3 )2 ] were obtained by slow evaporation technique. X-ray Diffraction powder, Scanning electron microscopy (SEM) and UV-Visible spectroscopy were used to characterize the purity, the morphology of the compound and the optical properties, respectively. PEA-CuCl4 crystallizes in Orthorhombic system, C2cb (n o  64) with a = 39.021(8) Å, b = 7.343 0(15) Å, c = 7.393 9(15) Å and Z = 8. The 3D and 2D Hirshfeld Surfaces analysis reveals the importance of hydrogen bonding in the stability of the bulk. The optical study shows that the compound undergoes an indirect optical transition with phonon assisted Cu 2+ d-d transitions in the visible region, and presents an energy band gap of about Eg = 2.3 eV. In parallel, the electronic band structures, the electronic densities of states and the energy gap value (Eg = 1.99 eV) were calculated using DFT+U calculations. The calculated and experimental results are in good agreement.